Analisis Pengaruh Service Quality dan Sistem Informasi Sekolah terhadap Customer Satisfaction yang Berdampak pada Customer Loyalty Studi Kasus Sekolah Xyz - Kurniawan, Roni (Bina Nusantara University, 2014)
Education has a strategic role in preparing qualified future generations. Education has business potential that is reliable and promising, considering the timeless education, as well as the expectations of every parent to their children to have the access to the best education. Evolving world of education today isdemonstrated by the high rate of growth of established schools, especially private schools. Parents today are more savvy and critical in determining the best school for their children, taking into account various aspects, ranging from excellent schools, curriculum, learning systems, the facility to activities that make their children good personality and smart. A more selective attitude that makes private education institutions now have to be more innovative in order to compete. This study was conducted to determine how big the Service Quality and Information Systems School, affect Customer Satisfaction, which will have an impact on Customer Loyalty (Case Study at XYZ School). The study was conducted with data collection techniques in the form of questionnaires toa total of 100 respondents, using descriptive statistical calculations, where the data were analyzed by using electronic data processing methods with the support of SPSS 17.0 To measure the influence of independent variables on the dependent variable, then the path analysis (path analysis) was used. The results showed that the Service Quality and Information Systems School were contributing together, and significant in Customer Satisfaction. Service Quality, Information Systems and Customer Satisfaction of school together contributesignificantly to Customer Loyalty.